Successful Treatment of MDR Acinetobacter baumannii Meningitis in a Young Adult Patient With Intraventricular and Intravenous Polymyxin B‐Tigecycline Based Combinations: A Case Report - Md Abdur Rahim; Himel Kumar Biswas; Md Abdul Kader Zilani; Rama Biswas; Sirazul Haque Ershad (Clinical Case Reports)
ABSTRACT Multiple drug resistance to Acinetobacter baumannii infection treatment is a great challenge for neuro‐intensivists due to poor drug penetration through the blood–brain barrier (BBB). Fortunately, the intraventricular administration of polymyxin‐B and tigecycline seems to be effective; there are few case reports demonstrating the effectiveness of such treatments. Here, we report the case of a 24‐year‐old male who presented with fever and neck rigidity after intracranial drainage following lung infection caused by MDR Acinetobacter baumannii. Due to the presence of turbid CSF, the administration of the intrathecal (ITH) route polymyxin‐B and tigecycline is not possible. In this situation, the neuro‐intensivist decided to start intraventricular tigecycline and polymyxin‐B administration along with IV tigecycline and polymyxin‐B via the intraventricular route, which was feasible because the patient had an external ventricular drain (EVD) due to obstructive hydrocephalus caused by the neurosurgeon after excision of the tumor.